A comparison of "fei" and "aber" - Hinterwimmer, Stefan; Ebert, Cornelia (ZAS Papers in Linguistics, 2018)
This paper compares the modal particle fei (Schlieben-Lange, 1979; Thoma, 2009) with the modal particle/sentence adverb aber (not to be confused with the conjunction aber, ‘but’). Intuitively, both items express some form of contrast and correction. We will show that both are special among discourse particles in the following sense: They make a contribution that is interpreted at a level distinct from the level where at-issue content (Potts, 2005) is interpreted, as is standard for modal particles (see Gutzmann, 2015 and the references therein). But more interestingly, they exclusively relate to propositions that have not entered the Common Ground via being the at-issue content of an assertion made by the addressee. Keywords: discourse particles, assertions, at-issue content, presuppositions, conventional implicatures, conversational implicatures.